2016
DOI: 10.1007/s40789-016-0124-3
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite sodalite/ceramic membrane for pre-combustion CO2 capture: synthesis and morphological characterization

Abstract: Carbon capture and storage (CCS) is amongst the possible options to reduce CO 2 emission. In the application of CCS, CO 2 capture techniques such as adsorption and membrane system have been proposed due to less energy requirement and environmental benign than the absorption process. However, membrane system has drawbacks such as poor membrane reproducibility, scale-up difficulty and high cost of the membrane supports. In this study synthesis and characterization of nanocomposite sodalite (HS)/ceramic membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Silica sodalite synthesized via topotactic conversion of a silicate layer as a precursor is formed without organic matter, and therefore has accessible micropores [ 20 ]. Silica sodalite as a filler in the polymeric matrix could be the candidate that might out-perform the hydroxy sodalite in terms of membrane flux since it has more accessible pore space for permeation [ 21 ]. Therefore, there is a need for a cheap and reliable treatment method that could be used to safely remove hazardous contaminants such as phenols to a safer level.…”
Section: Introductionmentioning
confidence: 99%
“…Silica sodalite synthesized via topotactic conversion of a silicate layer as a precursor is formed without organic matter, and therefore has accessible micropores [ 20 ]. Silica sodalite as a filler in the polymeric matrix could be the candidate that might out-perform the hydroxy sodalite in terms of membrane flux since it has more accessible pore space for permeation [ 21 ]. Therefore, there is a need for a cheap and reliable treatment method that could be used to safely remove hazardous contaminants such as phenols to a safer level.…”
Section: Introductionmentioning
confidence: 99%
“…SOD membranes were prepared following a modified method of Miachon et al [24] as reported by Daramola et al [36]. A precursor solution of molar composition 5SiO 2 :0.5Al 2 O 3 :50Na 2 O:1005H 2 O and a pH of 14 was subjected to the pre-programmed temperature profiles shown in Figure 2.…”
Section: Preparation Of Sod Membranesmentioning
confidence: 99%
“…In nanocomposite membranes, there is a change in temperature which causes a change in the autogenous pressure within the autoclave. This change brought about by the interruption might have facilitated flow of precursor solution into the pore of the support, thereby resulting in the growth of SOD crystals that form the separative layer within the pores [36,37]. The formation of the separative zeolite layer within the pores of the ceramic support via pore plugging method controls the formation of defects and limits the growth of the crystals within the size of the pores.…”
Section: Membrane Characterizationmentioning
confidence: 99%
See 2 more Smart Citations